Meningkatkan Kemampuan Kognitif Anak melalui Percobaan Sains Sedarhana di Kelompok Bermain Pelangi Desa Pematang Gadung Kecamatan Mersam - Zulqarnain, Zulqarnain; Sukatin, Sukatin; Sapitri, Septiya Ayu (Institut Agama Islam Yasni Bungo, 2021)
Abstract The Research was intended to increase children’s cognitive abilities through simple science experiments In Rainbow Playgroup at RT.11 village Pematang Gadung District Mersam. This study is a class action research. Studies are conducted in 2 cycles and each cycle were performed 2 meetings. The subject of this study is five or six years old kids in the group B and 14 children, consisting of 7 girls and 7 boys. The method used for data collections was observation and documentation. The results show that a child’s cognitive abilities in the rainbow playgroup at the beginning of 41% action in which 2 childrens begin was to developed cognitive abilities. In the 1 1st meeting cycle 59% of the children grew to 4, and then in the 1 2nd meeting 68% of the children grown to 7. And the results of the 2 1st meeting cycle were 78% of the number of children growing to 11, and then in the 2 2nd meeting cycle the result was 86% of the children growing to 12. The difference in improvement on pre-cycle to cycle 1 is 27% and cycle 1 to cycle 2 is 18%. The result of this study has already met the achievement indicators by 80%. The results of this study suggest thst simple scientific methods of experimentation can improved children’s children’s cognitive abilities.